Star Excursion Balance Test in young athletes with back pain - Appiah-Dwomoh, E. K.; Müller, S.; Hadzic, M.; Mayer, F. (Sports, 2016)
The Star Excursion Balance Test (SEBT) is effective in measuring dynamic postural control (DPC). This research aimed to determine whether DPC measured by the SEBT in young athletes (YA) with back pain (BP) is different from those without BP (NBP). 53 BP YA and 53 NBP YA matched for age, height, weight, training years, training sessions/week and training minutes/session were studied. Participants performed 4 practice trials after which 3 measurements in the anterior, posteromedial and posterolateral SEBT reach directions were recorded. Normalized reach distance was analyzed using the mean of all 3 measurements. There was no statistical significant difference (p > 0.05) between the reach distance of BP (87.2 ± 5.3, 82.4 ± 8.2, 78.7 ± 8.1) and NBP (87.8 ± 5.6, 82.4 ± 8.0, 80.0 ± 8.8) in the anterior, posteromedial and posterolateral directions respectively. DPC in YA with BP, as assessed by the SEBT, was not different from NBP YA